Health Insurance in India - R. , Ramamoorthy (International Journal of Psychosocial Rehabilitation, 2019)
The concept of health insurance was in the year 1694 by Hugh the elder chamberlain from peter chamberlain family. In 19th century “Accident Assurance” began to be available which operated much like modern disability insurance. This payment model continued until the start of 20th century. During the middle to late 20th century traditional disability insurance evolved in to modern health insurance programmers. Healthcare in India is in a state of enormous transition increased income and health consciousness among the majority of the classes, price liberalization, reduction in bureaucracy, and the introduction of private healthcare financing drive the change